UPAYA PENYELESAIAN SENGKETA BARANG MILIK NEGARA BERUPA ASET TANAH PASCA GEMPA LOMBOK 2018 MELALUI PENDEKATAN PERSUASIF BERBASIS HAK ASASI MANUSIA [THE EFFORTS TO SETTLEMENT OF STATE-OWNED PROPERTY IN THE FORM OF LAND ASSETS POST THE 2018 LOMBOK EARTHQUAKE THROUGH A PERSUASIVE-BASED HUMAN RIGHTS APPROACH] - Yoga Pamungkas, Heru; Rahmat, Hayatul Khairul (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2023)
The 2018 Lombok earthquake caused great damage and loss to the community and the government, one of which occurred in Dusun Lias, Desa Genggelang, Kecamatan Gangga, Kabupaten Lombok Utara where there was a dispute over state property in the form of land assets. This study aims to explore the root causes of disputes over state property in the form of land assets and describe the steps for resolving state property disputes through a human rights-based persuasive approach. The research method used is a qualitative research method with a descriptive approach, meanwhile, data collection techniques are carried out through interviews, observation, and documentation. The results of the study show that the root cause of disputes over state property in the form of land assets originates from the occupation by the local community and the 2018 Lombok Earthquake damaged their homes and then BNPB provided assistance with Earthquake Resistant Houses but the land used was not legally owned. Meanwhile, the dispute resolution steps are carried out through mediation techniques with a persuasive approach while still prioritizing the fulfillment of human rights.